2010
DOI: 10.1111/j.1582-4934.2010.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between early embryo development and tumourigenesis

Abstract: With the recent substantial progress in developmental biology and cancer biology, the similarities between early embryo development and tumourigenesis, as well as the important interaction between tumours and embryos become better appreciated. In this paper, we review in detail the embryonic origin of tumour, and the similarities between early embryo development and tumourigenesis with respect to cell invasive behaviours, epigenetic regulation, gene expression, protein profiling and other important biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 47 publications
4
118
0
1
Order By: Relevance
“…As reported in our previous studies of a potential oncofoetal CRC biomarker, certain high-value biomarkers, including miRNAs, genes and cancer proteins, show embryonic characteristics [10][11][12][13] . Tumorigenesis and embryogenesis have been postulated to share certain common pathways 10 .…”
supporting
confidence: 62%
See 2 more Smart Citations
“…As reported in our previous studies of a potential oncofoetal CRC biomarker, certain high-value biomarkers, including miRNAs, genes and cancer proteins, show embryonic characteristics [10][11][12][13] . Tumorigenesis and embryogenesis have been postulated to share certain common pathways 10 .…”
supporting
confidence: 62%
“…Indeed, it has been widely observed that these genes and proteins are shared between the embryogenesis and tumorigenesis processes 20 . The increased proliferation rate and lack of differentiation in cancer cells resemble the physiological process of embryogenesis 10 . Following this theory, we focused on miRNAs that are more highly expressed in both foetal and CRC tissues than in normal tissues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The embryonic origin of tumors has been gaining ground in the past few decades (e.g., see review by Ma et al [188]), and attempts have begun to fight cancer from the perspective of developmental biology [189,190]. In fact, tumorigenesis and embryonic development were found to be related to each other [191][192][193][194][195].…”
Section: Embryogenesis and Tumorigenesismentioning
confidence: 99%
“…Numerous data indicate the similarity of carcinogenesis and early ontogeny in terms of both cell function and molecu lar genetic mechanisms [1]. Hepatocellular carci noma is a common type of malignant liver tumor with a rapidly progressing course and poor prognosis.…”
mentioning
confidence: 99%